Implementation and validation of free flaps in acute and reconstructive burn care - Ziegler, Benjamin; Hundeshagen, Gabriel; Warszawski, Jan; Gazyakan, Emre; Kneser, Ulrich; Hirche, Christoph (Medicina, 2021)
Microsurgical free flap reconstruction in acute burn care offers the option of reconstructing even challenging defects in a single stage procedure. Due to altered rheological and hemodynamic conditions in severely burned patients, it bears the risk of a higher complication rate compared to microsurgical reconstruction in other patients. To avoid failure, appropriate indications for free flap reconstruction should be reviewed thoroughly. Several aspects concerning timing of the procedure, individual flap choice, selection and preparation of the recipient vessels, and perioperative measures must be considered. Respecting these specific conditions, a low complication rate, comparable to those seen in microsurgical reconstruction of other traumatic limb defects, can be observed. Hence, the free flap procedure in acute burn care is a relatively safe and reliable tool in the armamentarium of acute burn surgery. In reconstructive burn care, microsurgical tissue transfer is routinely used to treat scar contractures. Due to the more robust perioperative condition of patients, even lower rates of complication are seen in microsurgical reconstruction.
Gesehen am 16.09.2021